2014
DOI: 10.1002/2014wr015559
|View full text |Cite
|
Sign up to set email alerts
|

An intercomparison of statistical downscaling methods used for water resource assessments in the United States

Abstract: Information relevant for most hydrologic applications cannot be obtained directly from the native-scale outputs of climate models. As a result the climate model output must be downscaled, often using statistical methods. The plethora of statistical downscaling methods requires end-users to make a selection. This work is intended to provide end-users with aid in making an informed selection. We assess four commonly used statistical downscaling methods: daily and monthly disaggregated-to-daily Bias Corrected Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
157
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 198 publications
(164 citation statements)
references
References 91 publications
5
157
2
Order By: Relevance
“…Coarsened CanRCM4 outputs are more spatially coherent (median I = 0.38) than the WFDEI observations (median I = 0.18). Univariate QDM maintains this unrealistic spatial coherence (median I = 0.33), which is consistent with results reported by Gutmann et al (2014). Conversely, MBCr leads to precipitation fields that are less coherent than observed (median I = 0.07).…”
Section: Spatial Precipitation Examplesupporting
confidence: 89%
See 2 more Smart Citations
“…Coarsened CanRCM4 outputs are more spatially coherent (median I = 0.38) than the WFDEI observations (median I = 0.18). Univariate QDM maintains this unrealistic spatial coherence (median I = 0.33), which is consistent with results reported by Gutmann et al (2014). Conversely, MBCr leads to precipitation fields that are less coherent than observed (median I = 0.07).…”
Section: Spatial Precipitation Examplesupporting
confidence: 89%
“…Overall, spatiotemporal statistics from MBCn match observed values more closely than the other methods. Hence, it may be feasible to use MBCn directly in downscaling applications, a practice that has been questioned for univariate quantile mapping (Maraun 2013;Gutmann et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other important sources of uncertainty are the statistical downscaling technique of the GCM output and the internal climate variability. Gutmann et al (2014) showed that different downscaling techniques each have their advantages and disadvantages. The technique employed here, bias-corrected spatial disaggregation (Wood et al, 2004), tends to overestimate the wet-day fraction and underestimate extreme events, which both can influence the hydrologic response of the catchment.…”
Section: Discussionmentioning
confidence: 99%
“…The representation of underlying (physical) principles of hydrological processes in the hydrologic model can thus have a profound effect on the results and conclusion of a study. Although uncertainty in hydrologic projections has already been discussed and investigated in the literature, studies usually focus on one source of uncertainty (Gutmann et al, 2014) or a limited number of catchments (Vidal et al, 2016;Addor et al, 2014;Dobler et al, 2012). Here, we investigate three sources of uncertainty (GCM forcing, hydrologic parameters, hydrologic model structure) in hydrologic projections for 605 basins throughout the contiguous US over a wide range of climates, in order to reveal spatial patterns in uncertainty.…”
Section: Introductionmentioning
confidence: 99%